Place in Therapy of the Newly Available Armamentarium for Multi-Drug-Resistant Gram-Negative Pathogens: Proposal of a Prescription Algorithm - Lorenzo Volpicelli; Mario Venditti; Giancarlo Ceccarelli; Alessandra Oliva (MDPI AG, 2021)
The worldwide propagation of antimicrobial resistance represents one of the biggest threats to global health and development. Multi-drug-resistant organisms (MDROs), including carbapenem-resistant non-fermenting Gram-negatives and Enterobacterales, present a heterogeneous and mutating spread. Infections by MDRO are often associated with an unfavorable outcome, especially among critically ill populations. The polymyxins represented the backbone of antibiotic regimens for Gram-negative MDROs in recent decades, but their use presents multiple pitfalls. Luckily, new agents with potent activity against MDROs have become available in recent times and more are yet to come. Now, we have the duty to make the best use of these new therapeutic tools in order not to prematurely compromise their effectiveness and at the same time improve patients' outcomes. We reviewed the current literature on ceftazidime/avibactam, meropenem/vaborbactam and cefiderocol, focusing on antimicrobial spectrum, on the prevalence and mechanisms of resistance development and on the main in vitro and clinical experiences available so far. Subsequently, we performed a step-by-step construction of a speculative algorithm for a reasoned prescription of these new antibiotics, contemplating both empirical and targeted use. Attention was specifically posed on patients with life-risk conditions and in settings with elevated prevalence of MDRO.